Managing Actual Problems of Peatsoils Associated with Soil Acidity - M Edi Armanto; M.S. Imanudin; Elisa Wildayana; Heri Junedi; Mohd. Zuhdi (Program Pascasarjana Universitas Sriwijaya, 2016)
Abstract: The research objective is to manage actual problems of peatsoils associated with soil acidity. The research has been conducted on peatsoils in river backswamps located in Subdistricts of East Pedamaran and Pedamaran, District of OKI South Sumatra. Soil sampling was taken in cultivated and uncultivated types of landuse; cultivated peatsoils consist of Site A (intercropping between oil palm and pineapple) and Site B (oil palm), uncultivated peatsoils are divided into Site C (peat forest), Site D (swamp bush) and Site E (swamp grass). The research resulted that actual problems of soil acidity is associated with base saturation, cations exchange capacity, soil organic matters and C/N ratio, balances of soil nutrients, and toxicity potency. The climatic condition and drought can accelerate the occurrence of actual problems of peatsoils associated with acidity peatsoils. Some ameliorant have been applied in order of importance in the fields, namely lime/dolomite, mineral soils, organic fertilizers, combustion ash, and volcanic ash. Application of ameliorant materials is capable to minimize the actual problems of peatsoils associated with soil acidity.Keywords: Managing, actual problems, peatsoils, acidityAbstrak (Indonesian): Tujuan penelitian ini adalah untuk mengelola masalah aktual tanah gambut yang terkait dengan keasaman tanah. Penelitian ini telah dilakukan pada tanah lebak gambut yang terletak di Kecamatan Pedamaran Timur dan Pedamaran, Kabupaten OKI Sumatera Selatan. Contoh tanah diambil berdasarkan jenis penggunaan lahan; untuk tanah gambut yang digarap dibagi menjadi Site A (tumpang sari antara kelapa sawit dan nanas) dan Site B (kelapa sawit), tanah gambut tidak digarap dibagi menjadi Site C (hutan gambut), Site D (rawa semak) dan Situs E (rumput rawa). Hasil penelitian menunjukkan bahwa masalah aktual keasaman tanah dikaitkan dengan kejenuhan basa, kapasitas kation tukar, bahan organik tanah dan C/N rasio, keseimbangan nutrisi tanah, dan potensi toksisitas. Kondisi iklim dan kekeringan dapat mempercepat terjadinya masalah aktual tanah gambut yang terkait dengan keasaman tanah. Amelioran yang telah diterapkan, yaitu kapur/dolomit, tanah mineral, pupuk organik, abu pembakaran, dan abu vulkanik. Bahan amelioran mampu meminimalkan masalah-masalah aktual tanah gambut yang terkait dengan keasaman tanah.Kata kunci: Mengelola, masalah aktual, tanah gambut, keasaman